Revisiting Young Children's Technological Learning Behavior within a Microsystem Context for Development of the Next Generation - Adi Suryani; Sonny Harry Budiutomo H.; Soedarso Soedarso; Khairun Nisa; Fairuz Zahirah Zihni Hamdan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Children nowadays are more likely than earlier generations to understand, get along with, and be comfortable with technology. Compared to children from the past, children nowadays can find basic technology like a laptop or mobile phone with less difficulty. In addition, they can see how adults use those devices. Children may develop tighter and more frequent relationships with the instruments as a result of these aspects. This research intends to investigate how two children learn to use the available technology. The study adopts a qualitative research method. The data are collected by interviewing the parents of two children. The study discovers that, from the viewpoint of their parents, youngsters are unknowingly gaining information through technology through both individual and peer playing. They begin to learn how to share, analyze independently, work together, and internalize information from their peers through this playing and learning. Children also practice trial-and-error learning, in which they try things out, fail occasionally, and then figure things out. Children also learn how to stimulate their interest and satisfy their curiosity by gaining and examining new knowledge. The study also emphasizes the important functions of a few enabling elements, such as family support, children's active participation, the social dynamics at school, and the link between the family and the school.